Rumensin helps to reduce the incidence and severity of legume bloat in cattle - Tiruvoor G. Nagaraja; M.P. Katz; L.R. Fina (Kansas Agricultural Experiment Station Research Reports, 1985)
Monensin at 300 mg and 450 mg per 1000 lbs body weight reduced the severity of alfalfa pasture bloat by 41.2 and 73.1 %, respectively. Lasalocid at the same levels reduced the bloat score by 25.5 and 12.4%. The difference between the two antibiotics appears to be in their ability to inhibit rumen protozoa. Monensin reduced protozoal population in the rumen, whereas lasalocid had no effect. A smaller protozoal population decreases compounds that contribute to frothiness and also increases substances such as plant chloroplasts, which have antifrothing properties.; Dairy Day, 1985, Kansas State University, Manhattan, KS, 1985;
Keywords: Kansas Agricultural Experiment Station contribution; no. 86-94-S; Report of progress (Kansas Agricultural Experiment Station); 484; Dairy; Rumensin; Bloat; Protozoa; Alfalfa